Persistence of postoperative pain due to extrusion of endodontic obturator plastic carrier: A report of two cases treated with a periradicular microsurgical approach - Silvio Taschieri; Gianluca Gambarini; Irina Makeeva; Svetlana Tarasenko; Stefano Corbella (Wolters Kluwer Medknow Publications, 2021)
The aim of the present study was to describe two clinical cases showing postoperative pain associated with the use of plastic carrier obturation system and apical bone fenestration. The patients were treated by surgical access and apicoectomy through a modern technique (using magnification and microsurgical approach), thus removing the direct contact between obturation material and submucosal connective tissue. The surgical interventions were carried on without the occurrence of any complication. Postsurgical adverse sequelae were negligible. After few weeks from the surgery, all symptoms disappeared. Radiographic healing was observed after 48 months. The presence of apical bone fenestration could be the cause of persistent pain after root canal treatment. The contact between plastic carrier and submucosal connective tissue could be the direct cause of spontaneous pain even in absence of periapical infection. Since the clinical diagnosis could be difficult, the use of tridimensional radiology could be justified. Surgical approach, by the removal of the contact between the carrier and connective tissues, can be considered a viable option to treat these particular affections.